The Effect of Interactive Media and Power Point Media on the Early Ability of Vocational School Students: Pengaruh Media Interaktif Dan Media Power Point Terhadap Kemampuan Awal Siswa SMK - harleni herleni (Perkumpulan Doktor Indonesia Maju (PDIM), 2020)
Vocational High School (SMK) is a form of formal education unit that organizes vocational education at the secondary education level. Vocational learning is more for students. So the vocational training must be interactive. But Vocational Learning is currently not interactive and boring. So that makes learning outcomes of vocational students to be decreased. The approach in this study is quantitative. The method used in this study is the All Experiment. The subjects of the study were students of SMK Negeri 6 Padang. The results of this study prove that: 1) Student learning outcomes taught using interactive media are higher than students taught using Power Point media on KKPI subjects. 2) Student learning outcomes of high initial and low initial abilities taught using interactive media are higher than high initial and low ability students taught using Power Point media on KKPI subjects. 3) There is no interaction between learning media and initial ability to influence student learning outcomes in KKPI subjects.